The Scientific Aspects of the Balinese Wariga Calendar - I Made Tirta; I Wayan Windu Sara; Anak Agung Istri Ratnadewi (Faculty of Mathematics and Natural Sciences, University of Jember, 2026)
The Balinese Calendar, known as the Wariga Calendar, played a significant role in the religious and cultural life of Hindus, particularly in Bali. It was commonly found in Balinese Hindu households and remained an important reference for Balinese Hindus living outside the island. The Wariga Calendar represented a unique integration of Hindu philosophical values with scientific and mathematical calculations. One of its primary functions was determining the cycles of Hindu holy days and major festivals, including Saraswati, Pagerwesi, Galungan, and Kuningan. The introduction of the Wariga Calendar, especially its scientific and mathematical aspects, was considered important for Hindu Religious Education teachers throughout Indonesia. First, the holy days calculated using the Wariga Calendar had been celebrated by Hindu communities across the Indonesian archipelago, not only by the Balinese ethnic community. Second, only a limited number of Hindu Religious Education teachers outside Bali understood the mathematical principles underlying the calendar system. An introduction to the Wariga Calendar was delivered during a National Technical Guidance Program (Bimbingan Teknis) for Hindu Religious Education teachers held in a hybrid format on 2–3 August 2025. The program involved participants from various regions of Indonesia. The results showed that most participants considered the knowledge valuable for improving their understanding of the cyclical nature of Hindu holy days. Furthermore, many participants recognized that several elements of the Wariga Calendar exhibited mathematical patterns that were closely aligned with the philosophical messages embedded in the calendar, particularly those associated with the Galungan festival.